2019
DOI: 10.1038/s41598-019-48037-z
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin nanovehicle for targeted delivery of cytochrome C to cancer cells

Abstract: In this work, we have exploited the unique properties of a chimeric archaeal-human ferritin to encapsulate, deliver and release cytochrome c and induce apoptosis in a myeloid leukemia cell line. The chimeric protein combines the versatility in 24-meric assembly and cargo incorporation capability of Archaeglobus fulgidus ferritin with specific binding of human H ferritin to CD71, the “heavy duty” carrier responsible for transferrin-iron uptake. Delivery of ferritin-encapsulated cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…Besides, AfFtn is unique in its tetrahedral quaternary structure and the presence of four large triangular pores with a diameter of about 45 Å (~2500 Å 2 pore area), which provide the possibility for large cargos to enter its cavity [36]. Coupled with the negatively charged interior of AfFtn, a highly positively charged green fluorescent protein (GFP) variant (+36GFP, pI 10.4), several enzymes (human carbonic anhydrase II and the artificial (retro-)aldolase RA95.5-8F and Kemp eliminase HG3.17) genetically fused to +36GFP [61], and cytochrome C (pI = 10.8) [62] can be encapsulated within the ferritin cavity by simply mixing with protein solution containing NaCl/MgCl 2 . Through quantitative analysis, each protein cage can accommodate five GFP molecules or two to three GFP-enzyme complex molecules or 1.4 cytochrome C. However, it may not be suitable for the encapsulation of multimeric or highly negatively charged enzymes owing to the relatively small size of the cavity and/or reduced electrostatic attraction [61].…”
Section: Self-assembly Of Ferritin Controlled By Different Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, AfFtn is unique in its tetrahedral quaternary structure and the presence of four large triangular pores with a diameter of about 45 Å (~2500 Å 2 pore area), which provide the possibility for large cargos to enter its cavity [36]. Coupled with the negatively charged interior of AfFtn, a highly positively charged green fluorescent protein (GFP) variant (+36GFP, pI 10.4), several enzymes (human carbonic anhydrase II and the artificial (retro-)aldolase RA95.5-8F and Kemp eliminase HG3.17) genetically fused to +36GFP [61], and cytochrome C (pI = 10.8) [62] can be encapsulated within the ferritin cavity by simply mixing with protein solution containing NaCl/MgCl 2 . Through quantitative analysis, each protein cage can accommodate five GFP molecules or two to three GFP-enzyme complex molecules or 1.4 cytochrome C. However, it may not be suitable for the encapsulation of multimeric or highly negatively charged enzymes owing to the relatively small size of the cavity and/or reduced electrostatic attraction [61].…”
Section: Self-assembly Of Ferritin Controlled By Different Chemicalsmentioning
confidence: 99%
“…Therefore, ferritin nanocage has been developed into a bio-template for the encapsulation and delivery of anticancer drugs and tumor imaging agents, and applied in chemotherapy, photothermal therapy, and vivo imaging. Until now, several metallodrugs including cisplatin, carboplatin, oxaliplatin [55,122,123], Auoxo3 [92], Auoxo4, Au2phen [93], 4-PF6 [94], NAMI A [89], Ru(II)(η 6 -p-cymene) [ [96], as well as non-metallic drugs including DOX [21], curcumin [124], and cytochrome C [62], have been encapsulated in ferritin cavity to improve their bioavailability, tumor-selectivity, and cellular permeability and reduce the toxicity to normal cells. Guo and co-workers first proposed the cisplatin encapsulation and explored the cell absorption of ferritin-cisplatin nanoparticles (NPs) and their applications in tumor therapy.…”
Section: Applications In Medicine and Diagnosticsmentioning
confidence: 99%
“…The first application of this chimeric ferritin was the delivery of cyt C (cytochrome C) to acute lymphoid leukemia cells [41]. Cyt C is a small basic protein capable of inducing apoptosis when released from the mitochondria into the cytosol, where it interacts with Apaf-1, thus activating the caspase cascade.…”
Section: Archaeoglobus Fulgidus-human Chimeric Ferritin For Targeted mentioning
confidence: 99%
“…In addition, the same site allows the cavity to be functionalized, finetuning the internal charge of the cage according to the chemical-physical properties of the substance to be encapsulated. Macone et al [41] showed that this chimeric ferritin is indeed able to encapsulate cyt C and to deliver it to acute lymphoid leukemia cells expressing high levels of TfR1. This is noteworthy as these cells are practically resistant to any type of known transfection.…”
Section: Archaeoglobus Fulgidus-human Chimeric Ferritin For Targeted mentioning
confidence: 99%
See 1 more Smart Citation